205k views
4 votes
How do i find f(a+b) ?

How do i find f(a+b) ?-example-1

1 Answer

5 votes

Answer:

See explanation below.

Explanation:

f(x) = x^3 + 7x - 4

f(a + b) = (a + b)^3 + 7(a + b) - 4

= (a + b)(a + b)(a + b) + 7a + 7b - 4

= (a + b)(a^2 + ab + ab + b^2) + 7a + 7b - 4

= (a + b)(a^2 + 2ab + b^2) + 7a + 7b - 4

= (a^3 + 2ba^2 + ab^2 + ba^2 + 2ab^2 + b^3) + 7a - 4

= a^3 + b^3 + 3ba^2 + 3ab^2 + 7a - 4

Hope this Helps!! Have an Awesome Day!! (-:

User Brian Booth
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.